Measurement of B-c(2S)(+) and B-c*(2S)(+) cross section ratios in proton-proton collisions at root s=13 TeV - Yetkin, Elif Aslı (Amer Physical Soc., 2020)
The ratios of the B-c (2S)(+) to B-c(+), B-c(*)(2S)(+) to B-c(+), and Bc(2S)(+) to Bco2STHORNthorn production cross sections are measured in proton-proton collisions at root s = 13 TeV, using a data sample collected by the CMS experiment at the LHC, corresponding to an integrated luminosity of 143 fb(-1). The three measurements are made in the Bthornc meson phase space region defined by the transverse momentum p(T) > 15 GeV and absolute rapidity vertical bar y vertical bar < 2.4, with the excited B-c((+)) (2S)(+) states reconstructed through the B-(c)(+) p thornp-, followed by the Bthornc. J=.pthorn and J=.. mu thorn mu- decays. The Bc o2STHORNthorn to Bthornc, B-c(+) (2S)(+) to Bthornc, and B-c((+)) (2S)(+) to B-c((+)) (2S)(+) cross section ratios, including the unknown B-c(+) (2S)(+). Bc ->((+)) pthorn p- branching fractions, are o3.47 +/- 0.63(stat) +/- 0.33o(syst))%, (4.69 +/- 0.71)(stat)(+) +/- 0.56(syst))%, and 1.35 +/- 0.32((stat)) +/- 0.09((syst)), respectively. None of these ratios shows a significant dependence on the pT or jyj of the B-c(+) meson. The normalized dipion invariant mass distributions from the decays B-c((*))(2S)+ -> B-c((*))pi(+)pi(-) are also reported.
21 pages